Neonatal arrhythmias: diagnosis, treatment, and clinical outcome - Ji-Eun Ban (Korean Pediatric Society, 2017)
Arrhythmias in the neonatal period are not uncommon, and may occur in neonates with a normal heart or in those with structural heart disease. Neonatal arrhythmias are classified as either benign or nonbenign. Benign arrhythmias include sinus arrhythmia, premature atrial contraction, premature ventricular contraction, and junctional rhythm; these arrhythmias have no clinical significance and do not need therapy. Supraventricular tachycardia, ventricular tachycardia, atrioventricular conduction abnormalities, and genetic arrhythmia such as congenital long-QT syndrome are classified as nonbenign arrhythmias. Although most neonatal arrhythmias are asymptomatic and rarely life-threatening, the prognosis depends on the early recognition and proper management of the condition in some serious cases. Precise diagnosis with risk stratification of patients with nonbenign neonatal arrhythmia is needed to reduce morbidity and mortality. In this article, I review the current understanding of the common clinical presentation, etiology, natural history, and management of neonatal arrhythmias in the absence of an underlying congenital heart disease.